2017
DOI: 10.15420/cfr.2017:12:1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Post-discharge Mortality Among Patients Hospitalized for Acute Heart Failure

Abstract: Acute Heart Failure (AHF) is a " multi-event disease" and hospitalisation is a critical event in the clinical course of HF. Despite relatively rapid relief of symptoms, hospitalisation for AHF is followed by an increased risk of death and re-hospitalisation. In AHF, risk stratification from clinically available data is increasingly important in evaluating long-term prognosis. From the perspective of patients, information on the risk of mortality and re-hospitalisation would be helpful in providing patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…The main findings of the present study are as follows: (1) previous history of HF hospitalization in patients hospitalized for ADHF was associated with a higher risk for mortality;…”
Section: Discussionmentioning
confidence: 61%
“…The main findings of the present study are as follows: (1) previous history of HF hospitalization in patients hospitalized for ADHF was associated with a higher risk for mortality;…”
Section: Discussionmentioning
confidence: 61%
“…The survival benefit of beta blockade was more evident in patients surviving the first month after discharge. This could be explained by the fact that the rate of early mortality is especially high in elderly patients [31], and that beta-blockers were added on during the early follow-up periods. A previous study in chronic HF patients also reported that a quarter of admitted HF patients stopped beta-blockers or reduced their dosage at discharge due to hypotension of use of inotropes [32].…”
Section: Octogenarians With Hfpefmentioning
confidence: 99%
“…A comprehensive assessment in these patients is necessary to identify prognostic characteristics that may become possible therapeutic targets. In RCTs and registries, the predictive factors for post-discharge mortality included age, history of previous hospitalization, congestion, systolic blood pressure, heart rate, QRS duration, renal function, markers of organ injury, and non-cardiac comorbidities (such as diabetes, cerebrovascular disease, chronic obstructive pulmonary disease, liver cirrhosis, and iron deficiency)(97).…”
Section: Prognosismentioning
confidence: 99%